Anti-Corruption Education in Shipping Universities: Efforts to BuildIntegrity in the Maritime Industry: Pendidikan Anti Korupsi di dalam Perguruan Tinggi Pelayaran:Upaya Membangun Integritas dalam Industri Maritim - Nuriyanti; David, Muhammad; Adi, Panggi Nur; Romadhoni, Dita; Nurdiyanti, Aina (PT. Alpha Trianguli Australis, 2024)
The aim of this research is to explore the strategies and approaches used by shipping universities to teach anti-corruption practices and build integrity in the maritime industry. The study was carried out using a descriptiveanalytical research model that involved reviewing relevant literature and sources of information. The findings of this research suggest that anticorruption education should be an essential part of maritime education. Effective educational strategies include the use of real-life case studies, simulations of corruption scenarios, and collaborative learning to enhance students' understanding of corruption risks in the maritime context. A holistic approach is also adopted, which involves collaboration with industry, establishing a code of ethics, and cultivating the values of integrity. The research results indicate that implementing this approach can produce graduates who are more aware of anti-corruption practices, promote integrity, and contribute to improving ethics in the maritime industry.